Rupture and Reconstruction The Transformation of Modern Orthodoxy. (The Littman library of Jewish civilization, 2021)
A cogent analysis of Orthodoxy's 'swing to the right': a rupture with existing attitudes and patterns of behaviour that has had major consequences for Jewish society and spirituality. This new edition deals with criticisms raised since the essay, long established as a classic in the field, was originally published.